Simple and Fast Reoptimizations for the Steiner Tree Problem - Escoffier, Bruno; Milanič, Martin; Paschos, Vangelis (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2009)
We address reoptimization issues for the Steiner tree problem. We assume that an optimal solution is given for some instance of the problem and the objective is to maintain a good solution when the instance is subject to minor modifications, the simplest such modifications being vertex insertions and deletions. We propose fast reoptimization strategies for the case of vertex insertions and we show that maintenance of a good solution for the “shrunk” instance, without ex nihilo computation, is impossible when vertex deletions occur. We also provide lower bounds for the approximation ratios of the reoptimization strategies studied.